Do voluntary sustainability standards improve socioeconomic and ecological outcomes? Evidence from Ghana's cocoa sector - Marlene Yu Lilin Wätzold; Issaka Abdulai; Amanda Cooke; Katharina Krumbiegel; Carolina Ocampo-Ariza; Arne Wenzel; Meike Wollni (Georg-August University of Göttingen, RTG 2654 Sustainable Food Systems, 2024)
Voluntary sustainability standards offer potential for sustainable development by improving the livelihoods of smallholder cash crop farmers while conserving biodiversity. However, their overall implications remain poorly understood, as studies have mostly focused on assessing their effects on single sustainability dimensions. Here, we use an interdisciplinary approach to understand the simultaneous effects of sustainability standards on socioeconomic and ecological outcomes in Ghana's cocoa sector. Our study is based on a rich dataset comprising representative household data from 814 smallholder cocoa-producing households from five major cocoa regions and ecological data from 119 cocoa plots. Results from the endogenous switching regression approach suggest that sustainability standards have positive effects on socioeconomic outcomes such as cocoa yield, net cocoa income and net returns to land. However, using generalized linear mixed effects models, we do not find any significant associations with ecological outcomes related to vegetation structure and animal diversity. Our results indicate that sustainability standards in Ghana's cocoa sector lead to socioeconomic benefits but not to ecological benefits for the plot environment. Nevertheless, yield increases do not come at the expense of biodiversity. We conclude that sustainability standards have the potential to improve socioeconomic outcomes, without significantly creating trade-offs with ecological outcomes.
Keywords: Q01; Q56; Q57; 330; Sustainability standards; Certification; Cocoa; Ghana; Biodiversity; Trade-offs